Characterization of the brain 26S proteasome and its interacting proteins - Tai, Hwan-Ching; Besche, Henrike; Goldberg, Alfred L.; Schuman, Erin M. (Frontiers in Molecular Neuroscience, 2010)
Proteasome-mediated proteolysis is important for synaptic plasticity, neuronal development, protein quality control, and many other processes in neurons. To define proteasome composition in brain, we affinity purified 26S proteasomes from cytosolic and synaptic compartments of the rat cortex. Using tandem mass spectrometry, we identified the standard 26S subunits and a set of 28 proteasome-interacting proteins that associated substoichiometrically and may serve as regulators or cofactors. This set differed from those in other tissues and we also found several proteins that associated only with either the cytosolic or the synaptic proteasome. The latter included the ubiquitin-binding factor TAX1BP1 and synaptic vesicle protein SNAP-25. Native gel electrophoresis revealed a higher proportion of doubly-capped 26S proteasome (19S-20S-19S) in the cortex than in the liver or kidney. To investigate the interplay between proteasome regulation and synaptic plasticity, we exposed cultured neurons to glutamate receptor agonist NMDA. Within 4 h, this agent caused a prolonged decrease in the activity of the ubiquitin-proteasome system as shown by disassembly of 26S proteasomes, decrease in ubiquitin-protein conjugates, and dissociation of the ubiquitin ligases UBE3A (E6-AP) and HUWE1 from the proteasome. Surprisingly, the regulatory 19S particles were rapidly degraded by proteasomal, not lysosomal degradation, and the dissociated E3 enzymes also degraded. Thus the content of proteasomes and their set of associated proteins can be altered by neuronal activity, in a manner likely to influence synaptic plasticity and learning.